Automation 2.0: The Impact of Artificial Intelligence - Ishaanvi Thakur (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
Automation has been a key driver of productivity and efficiency in various industries, but the advent of artificial intelligence (AI) has taken automation to the next level. Automation 2.0, as it is often referred to, combines traditional automation technologies with AI and machine learning to create a new generation of intelligent automation systems. These systems can learn from data, adapt to new situations, and make decisions autonomously, enabling them to perform tasks that were previously impossible or impractical. The impact of AI on automation, highlighting the benefits and challenges of this new generation of automation systems. We discuss the ways in which AI is being used to improve the efficiency and effectiveness of automation, including the use of machine learning algorithms to optimize process control, the integration of AI-powered sensors and actuators, and the development of autonomous systems that can operate independently. We also examine the potential applications of Automation 2.0, including the use of AI-powered robots in manufacturing, the integration of AI with industrial control systems, and the development of autonomous vehicles and drones. Finally, we discuss the challenges and limitations of Automation 2.0, including the need for high-quality data, the potential for bias and error, and the need for ongoing training and maintenance.